2015
DOI: 10.1007/s00204-015-1526-5
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations in human blood of petroleum hydrocarbons associated with the BP/Deepwater Horizon oil spill, Gulf of Mexico

Abstract: During/after the BP/Deepwater Horizon oil spill, cleanup workers, fisherpersons, SCUBA divers, and coastal residents were exposed to crude oil and dispersants. These people experienced acute physiological and behavioral symptoms and consulted a physician. They were diagnosed with petroleum hydrocarbon poisoning and had blood analyses analyzed for volatile organic compounds; samples were drawn 5-19 months after the spill had been capped. We examined the petroleum hydrocarbon concentrations in the blood. The aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 44 publications
0
7
0
1
Order By: Relevance
“…To our knowledge, only one other study has compared blood BTEX levels among Gulf state residents exposed to the DWH oil spill with levels in NHANES ( 51 ). Sammarco et al ( 51 ) concluded that blood BTEX levels (except for o-xylene) in their study population were significantly higher than NHANES 95 th percentiles. However, the study was smaller (69 people), lacked any information on smoking, and measured blood levels closer in time to the oil spill (5–19 months after the well was capped).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only one other study has compared blood BTEX levels among Gulf state residents exposed to the DWH oil spill with levels in NHANES ( 51 ). Sammarco et al ( 51 ) concluded that blood BTEX levels (except for o-xylene) in their study population were significantly higher than NHANES 95 th percentiles. However, the study was smaller (69 people), lacked any information on smoking, and measured blood levels closer in time to the oil spill (5–19 months after the well was capped).…”
Section: Discussionmentioning
confidence: 99%
“…In the wake of this crisis, most toxicological studies have focused on the effects of PAHs in the oil organics and dispersants. While these aspects are indeed important to understand, few health effects have been linked to PAH levels from this crisis (Carmichael et al, 2012; Fitzgerald and Gohlke, 2014; Schwacke et al, 2014; Lane et al, 2015; Millemann et al, 2015; Sammarco et al, 2015). This outcome may reflect the unique ecosystem of the Gulf of Mexico as one with some resilience to oil, due to the large amounts of oil that naturally seeps from the sea floor.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Over a span of three months, the spill contaminated more than 68,000 square miles, ranging from Texas to Florida. [4][5][6] This resulted in damages to ecosystems in affected areas, causing widespread impacts on both the tourism and fishing industries. 3 Several thousand workers and volunteers helped with oil spill cleanup activities.…”
Section: Impacts and Health Effects Of The Deepwater Horizon Oil Spillmentioning
confidence: 99%